HUBUNGAN ANTARA INDEKS MASSA TUBUH DAN KEBERHASILAN STIMULASI OVARIUM PADA PROGRAM FERTILISASI IN VITRO â TRANSFER EMBRIO - , Rosana YaQualine, dr. Shofwal Widad, SpOG(K) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Obesity and overweight is becoming a major problem all over the world. Obesity is associated with abnormalities in sex steroid hormones balance through mechanism of insulin resistance and hyperinsulinemia that cause the anovulatoar infertility condition. Imbalance in sex steroid hormones affects ovarian response to stimulation in fertilisation in vitro programme. Design: Observational retrospective cohort Location of study: Infertility Clinic of Permata Hati, dr. Sardjito Hospital, Yogyakarta. Result: A total of 71 cycles from 71 couples who undergoing IVF were included in the study according to inclusion and exclusion criteria. Cut off point for BMI is 25 kg/m2. Thereâs no difference in respons to ovarian stimulation between high and low BMI (RR 1,176